Roles of small RNAs in the establishment of tolerant interaction between plants and viruses - Kriznik, M.; Baebler, S.; Gruden, K.
In a tolerant plant-virus interaction, viral multiplication is sustained without substantial effects on plant growth or reproduction. Such interactions are, in natural environments, frequent and sometimes even beneficial for both interactors. Here we compiled evidence showing that small RNAs modulate plant immune responses and growth, hence adjusting its physiology to enable a tolerant interaction. Importantly, the role of small RNAs in tolerant interactions resembles that required for establishment of a mutualistic symbiosis. Tolerance can become a sustainable strategy for breeding for virus resistance as selection pressure for emergence of more aggressive strains is low. Understanding the processes underlying establishment of tolerance is, therefore, important for the development of future crops.